Parental involvement: Is it worthwhile to invest in family-faculty coalition for primary level EFL learning? - Mimosa Mabin; Sukanto Roy (Universitas Merdeka Malang, 2023)
This study deals with the significance of parental involvement in students’ English learning. It centres its focus primarily on the students and tries to explore their take on their parents’ participation regarding L2 learning and also wishes to uncover some effective methods that might be used by parents to facilitate children’s English language learning. The findings indicate that students viewed the support from their family while learning English as something nonexpendable. Not only did parents’ active involvement leave a mark on students’ academic achievement, but also it seemed to affect the students’ psychology positively. Students with a higher degree of parental involvement, in the study, displayed greater self-confidence while interacting in the target language and also were appreciative of the support that they received from home. Contrarily, their counterparts, who did not have any noteworthy assistance from their parents, regretted not having it and saw it as an obvious drawback in their L2 learning. The study also shows that parents simply reading storybooks, watching English movies, or playing word games with their children aids English learning. Hence, recommendations were made to introduce parental involvement more extensively and as an academic and instructional mechanism for more productive L2 learning.